If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4m + 3 = 16 Reorder the terms: 3 + 4m = 16 Solving 3 + 4m = 16 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 4m = 16 + -3 Combine like terms: 3 + -3 = 0 0 + 4m = 16 + -3 4m = 16 + -3 Combine like terms: 16 + -3 = 13 4m = 13 Divide each side by '4'. m = 3.25 Simplifying m = 3.25
| 2(-2)+3y=-4 | | 2x+3(0)=-4 | | 3(y-6)-2(5+3y)=5 | | 2(y+6)+1=3y+12-y | | X*4+6=20 | | 8(-1.25)-3y=-10 | | 2x^2-5x=-2is | | 8x-3(0)=-10 | | 3/1*8/9*4/11 | | 2x^2+mx=-2 | | 1/5*3/4*5/7 | | 2(y+6)=3y+12-y | | 5-3(x+2)=2x-7 | | -9+15=3x-18 | | 4x+y=3x+12 | | (X-1)+(x)+(x+1)=48 | | x/9=20/36 | | t(n)=7n+1 | | 5x-2x+4=3x+5 | | 4x+2x=3+5 | | 7y-2=4+3y | | 3x-82=23 | | 5x+9x=66 | | M+1-3m+7=0 | | -7x+6+5x=2x+11 | | 64(n)=8 | | 0.96./0.06 | | 4(5x-3)=-132 | | -4n+-8=-12+8 | | 21=0.75+m | | 3-5x=9-4x | | 8b^2+6b-192=0 |